Cerebrospinal Fluid Biomarkers and Prediction of Conversion in Patients with Mild Cognitive Impairment: 4-Year Follow-Up in a Routine Clinical Setting - Alessia Lanari; Lucilla Parnetti (The Scientific World Journal)
Mild cognitive impairment (MCI) is a very common syndrome in elderly people, with a high risk of conversion to dementia. Several investigations have shown the usefulness of cerebrospinal fluid (CSF) biomarkers (Aβ42, total tau [T-tau], and phosphorylated tau [P-tau]) in predicting the progression to Alzheimer's disease (AD). We report a 4-year follow-up of MCI patients who underwent CSF evaluation for biomarker assessment, in order to further evaluate the usefulness of CSF analysis in predicting the conversion to dementia in a routine clinical setting. We identified 55 patients with MCI among the consecutive patients, referred from 2001 to 2003 to our Memory Clinic for cognitive disorders, who underwent a complete diagnostic assessment, including lumbar puncture (n = 273). At the end of the follow-up, 31 MCI patients (56%) did not progress to dementia (stable MCI), while 24 (44%) developed a dementia condition. At baseline, the mean levels of CSF Aβ42, T-tau, and P-tau were significantly altered in MCI patients who were converting to dementia with respect to those with stable MCI. All MCI patients with the three altered CSF biomarkers developed dementia within 1 year. Among the stable MCI patients, none showed all three pathological values and only one subject had the pathological value of P-tau. Early diagnosis of dementia and, specifically, a correct prediction of MCI outcome represent a primary goal. To this respect, the role of CSF biomarkers seems to be crucial in a routine clinical setting.